PROSPECTOR-DEFENDER STRATEGY, AUDITOR INDUSTRY SPECIALIZATION, EARNINGS MANAGEMENT THROUGH REAL ACTIVITIES, AND EARNINGS QUALITY - Wuryan Andayani; Sony Warsono (Journal of Indonesian Economy and Business (JIEB), 2013)
This study observed the influence of the company prospector-defender strategy and auditor industry specialization toward the earnings management through real activities and earnings quality. An important finding in this study confirmed that the auditor industry specialization could not restrict the earnings management and the company‘s prospector strategy could restrict the earnings management. On the contrary, defender strategy could not restrict the earnings management. Another finding proved that the auditor industry specialization influence the earnings response coefficient (ERC) and investors’ response. Besides the auditor industry specialization, as well as the prospector and defender strategies, other factors also affected influence ERC are leverage, company size, stock return, beta and market return. The interaction among the prospector and defender strategies and unexpected earnings neither influence the CAR nor the investors’ response. This was probably because the investors pay attention to the strategy used by the company. However, there were any interaction variables: industry specialization auditor, leverage, stock return, beta and market return influence the CAR and investors’ response.